Optimalisasi Proses Pengeringan Minyak dengan Inovasi Teknologi Spinner untuk Meningkatkan Daya Saing Produk Keripik Lokal - Alwi Shahab, Mohammad; Baiq Rika Ayu Febrilia; Sri Mulyawati; I Gusti Ngurah Aryawan Asasandi; Dyah Ayu Suryaningrum (Universitas Mataram, 2025)
Abstract: This community engagement program aims to enhance the capacity of the Nine Seru Women Farmers Group (Kelompok Wanita Tani/KWT) in agricultural product processing through the introduction of Spinner technology as a solution to optimize the oil-draining process in chip production. Manual production methods previously used were found to be inefficient and negatively affected product quality and competitiveness. Through a participatory approach, this initiative involved needs assessment, preparation of training materials, and the implementation of technical training using hands-on learning methods. Evaluation results demonstrated a significant improvement in participants' knowledge and skills, as evidenced by the comparison of pre-test and post-test scores and field observations. The Spinner technology effectively accelerated the oil-draining process, reduced excess oil content, and improved the final product’s quality. This initiative highlights that appropriate technology interventions, when tailored to local needs and delivered through active learning methods, can be an effective strategy for empowering rural women and enhancing household-based agro-industries. Continued training, technology diversification, and multi-stakeholder collaboration are essential to ensure the sustainability and growth of micro-scale agricultural enterprises.